2020
DOI: 10.1002/pat.5042
|View full text |Cite
|
Sign up to set email alerts
|

Cold atmospheric plasma modification of curcumin loaded in tri‐phosphate chitosan nanoparticles enhanced breast cancer cells apoptosis

Abstract: The anti-cancer mechanisms of curcumin have been reported to include suppressions of angiogenesis and tumor proliferation. The main goal of this research is to increase the solubility of curcumin by cold atmospheric plasma (CAP) and assess the effects of modified curcumin by charging with tri-polyphosphate chitosan nanoparticles for MCF-7, MDA-MB-231 breast cancer cells, and human fibroblast cells. Curcumin modification was done by CAP and its solubility was evaluated by spectrophotometry. After loading modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Recently, several reports have been published on the effectiveness of the combined use of CAP and nanoparticles on cancer [23][24][25][26][27][28]. However, there was no study carried out to investigate the effect of nZVI and CAP on metabolic activity and apoptosis of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several reports have been published on the effectiveness of the combined use of CAP and nanoparticles on cancer [23][24][25][26][27][28]. However, there was no study carried out to investigate the effect of nZVI and CAP on metabolic activity and apoptosis of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the previous studies in which NPs and CAP synergism has been explored, when metallic NPs, not loaded with any drug, were considered (such as gold NPs 25 , 28 , silver NPs 27 and iron NPs 61 , 62 ), CAP was found to enhance the activities acquired by NPs (when used) alone. In one report where curcumin-loaded NPs were used, CAP was applied as a practical approach to improve the aqueous solubility of curcumin during preparation of tri-phosphate chitosan nanoparticles TPP-NPs 26 . Curcumin TPP-NPs were not used in combination with CAP in the reported cell viability studies.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have revealed that certain types of cancer cells are more susceptible to CAP treatment and oxidative damage compared to normal cells [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], although the reported selectivity depends on cell type and culture medium [ 24 ]. CAP exhibits therapeutic potential against various types of cancer [ 25 ], including hepatocellular carcinoma [ 26 ], lung carcinoma [ 27 ], breast cancer [ 28 ], melanoma [ 18 ], glioblastoma [ 29 ], pancreatic cancer [ 30 ], and head and neck cancer [ 31 ]. Intracellular RONS levels induced by CAP treatment in cancer therapies can cause irreversible damage to cellular components, particularly proteins, lipids, and DNA, ultimately leading to tumor cell death [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%